2018
DOI: 10.3390/w10060724
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder Engagement in Maritime Spatial Planning: The Efficacy of a Serious Game Approach

Abstract: The 2014 EU Directive on Maritime Spatial Planning (MSP) lays down obligations for the EU Member States to establish a maritime planning process, resulting in a maritime spatial plan by 2020. Consultation should be carried out with local, national and transnational stakeholders. Stakeholder engagement in MSP is complex because of the great number and diversity of maritime stakeholders and the unfamiliarity of some of these stakeholders with MSP and its potential impact. To facilitate stakeholder engagement in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 21 publications
0
35
0
Order By: Relevance
“…Predominantly, the game-based approaches for water governance described in this SI aim to (a) facilitate understanding of the overall complexity of the real world; (b) foster stakeholder collaboration, cross-sectoral integration, and/or multi-stakeholder dialogue; (c) experiment with multiple scenarios in a safe trial environment; (d) facilitate capacity building; and (e) overall, enable single-to triple-loop learning [64][65][66][67][68][69][70][71][72]. These aims correspond mostly to phase 2 of the water governance process (i.e., create stakeholder awareness and trigger multi-stakeholder dialogue), as well as phase 4 (i.e., creating an enabling environment) ( Figure 2).…”
Section: Reasons For Using Game-based Approaches and Topics Addressedmentioning
confidence: 99%
See 1 more Smart Citation
“…Predominantly, the game-based approaches for water governance described in this SI aim to (a) facilitate understanding of the overall complexity of the real world; (b) foster stakeholder collaboration, cross-sectoral integration, and/or multi-stakeholder dialogue; (c) experiment with multiple scenarios in a safe trial environment; (d) facilitate capacity building; and (e) overall, enable single-to triple-loop learning [64][65][66][67][68][69][70][71][72]. These aims correspond mostly to phase 2 of the water governance process (i.e., create stakeholder awareness and trigger multi-stakeholder dialogue), as well as phase 4 (i.e., creating an enabling environment) ( Figure 2).…”
Section: Reasons For Using Game-based Approaches and Topics Addressedmentioning
confidence: 99%
“…The game-based approaches described in the SI papers focused on different water topics: Water supply safety plans at the watershed and household scales [64], water supply in peri-urban areas [66], local to transnational maritime spatial planning [65,67], flood mitigation in urban-rural watersheds [68], water resource management at the watershed scale [69], mangrove shrimp farming [70], the water-energy-food-land-climate nexus [71], how water managers perceive "models and interactive interfaces (serious games)" [72], and a review of games on the water cycle, water and aquatic ecosystem management, and the human right to water [73].…”
Section: Reasons For Using Game-based Approaches and Topics Addressedmentioning
confidence: 99%
“…Preliminary research [36] involving the SG AquaRepublica has shown that SG have the potential to stimulate the four stages of the knowledge co-creation process, and Barreteau, Le Page, and Perez [23] add that SG and gaming simulations offer a unique opportunity to facilitate decision-making processes. One type of SG used in environmental management combines computer simulations powered by environmental models with role-play as a method to address the complexity inherent to environmental problems, while promoting collaboration and learning among stakeholders [37][38][39]. By gamifying the experience, stakeholders are given the space to exchange perspectives, knowledge, and ideas in a low-stakes environment, allowing them to better understand the boundaries that separate them.…”
Section: Knowledge Co-creation and Stakeholder Engagementmentioning
confidence: 99%
“…Additionally, Van Bilsen, Bekebrede, and Mayer [42] found that as game-play progresses, trust builds between participants, which helps them articulate a common understanding of issues. One of the assumptions of game-based learning is that the learning that occurs via gameplay can sometimes be transferred to similar situations outside of the game [39]. To ensure that participants understand how they can use what they have learned during gameplay in a real-world setting, a debriefing session following a game event is particularly important [43,44].…”
Section: Knowledge Co-creation and Stakeholder Engagementmentioning
confidence: 99%
“…Although the problem has already been tackled in scientific publications, i.e., [8][9][10][11][12][13], the European Union does not have much experience in this regard yet. The EU Member States are currently at various stages of creating procedures related to maritime spatial planning [14], and experience in transboundary approaches is growing through official processes and pilot programs [15]. Due to the fact that there mainly were pilot programs conducted, the aim of this study is to analyze the existing legal regulations and to assess the national procedures resulting therefrom.…”
Section: Introductionmentioning
confidence: 99%